1989
DOI: 10.1159/000118578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drugs Acting on Monoaminergic and Cholinergic Systems on the Quantified EEG of Rats

Abstract: Five different classes of drugs (clonidine: 0, 0.10, 0.30, 0.50 mg/kg; yohimbine: 0, 2, 4, 8 mg/kg; haloperidol: 0, 0.02, 0.04, 0.08 mg/kg; piracetam: 0, 150, 300, 600 mg/kg, and eserine: 0, 0.10, 0.30, 0.50 mg/kg) were studied on two cortical EEG derivations as well as a deep structure, the locus ceruleus in the rats. Each drug affected the EEG in its own particular manner. Clonidine significantly decreased frequency in the theta band (3.7–7.5 Hz) and increased it in the alpha band (7.6–13.5 Hz). A general si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Patients with Alzheimer's disease treated with intravenous physostigmine showed a decrease in delta activity (Gustafson et al, 1987). Studies in male rats (Emilien, 1989) and male Japanese White rabbits (Yamamoto, 1988) have also shown a decreased power in the delta frequency band after physostigmine administration.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Alzheimer's disease treated with intravenous physostigmine showed a decrease in delta activity (Gustafson et al, 1987). Studies in male rats (Emilien, 1989) and male Japanese White rabbits (Yamamoto, 1988) have also shown a decreased power in the delta frequency band after physostigmine administration.…”
Section: Discussionmentioning
confidence: 99%
“…Drug‐induced EEG changes are generally accepted as a method of predicting the clinical potency of drugs. It has been shown that the human EEG can serve as a sensitive and valid measurement system in this regard [ 43]. Investigations in young healthy volunteers who received scopolamine have been shown that the drug influences the delta, theta, alpha and beta frequency bands in the EEG.…”
Section: Introductionmentioning
confidence: 99%